Mechanical performance of cement mortar with olive pomace aggregates and olive mill wastewater: an experimental investigation - EL Boukhari, M.; Merroun, O.; Maalouf, C.; Bogard, F.; Kissi, B. (Cogent Engineering, 2023)
This study investigates the potential use of olive aggregates (OA) in the production of cementitious materials as a substitute for natural sand to reduce excessive use of this resource. Two types of OA were used: OPA (olive pomace aggregates) and OPMW (OPA mixed with olive mill wastewater). The aim was to determine experimentally whether improvements in the mechanical properties of the produced lightened cement mortar could be obtained compared to the reference mortar. Laboratory tests were conducted on two series of mortar samples made by replacing 0%, 5%, 10%, and 15% of natural sand with both dry and saturated OA. The best results were observed in a mixture containing 5% of OPMW at the dry state, which had a marginal effect on the compressive strength of the produced mortar, reaching 33.50 MPa after 28 days of curing. However, microstructural analysis revealed low adhesion between the OA and the cement matrix at the interface transition zone (ITZ) after 28 days. Increasing the OA content was found to decrease the workability of the mixture while also increasing the porosity of the resulting lightened cement mortar. Additionally, the use of OA reduces ultrasonic pulse velocity and dynamic modulus of elasticity. Overall, the best results were obtained with the mixture containing 5% of OPMW at the dry state, which meets the standards for general use of building materials.
Keywords: Olive pomace aggregates; agricultural waste minimization; lightened cement mortar; lightweight aggregates; mechanical properties; olive mill wastewater; sustainable building materials